2016
DOI: 10.1186/s13045-016-0353-3
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal expansion of TCR Vδ T cells may be a potential immune biomarker for clinical outcome of acute myeloid leukemia

Abstract: BackgroundRecent data have shown that γδ T cells can act as mediators for immune defense against tumors. Our previous study has demonstrated that persisting clonally expanded TRDV4 T cells might be relatively beneficial for the outcome of patients with T cell acute lymphoblastic leukemia after hematopoietic stem cell transplantation (HSCT). However, little is known about the distribution and clonality of the TRDV repertoire in T cell receptor (TCR) of γδ T cells and their effects on the clinical outcome of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
(34 reference statements)
4
18
0
Order By: Relevance
“…Previous studies have shown different proliferation patterns of TCR subfamily T cells between different subtypes and different disease statuses in leukemia at the molecular level . In this study, we also found a different distribution pattern of TCR Vβ subfamily T cells, particularly PD‐1+ Vβ subfamily T cells, between M5 and the favorable prognosis subtype M3.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies have shown different proliferation patterns of TCR subfamily T cells between different subtypes and different disease statuses in leukemia at the molecular level . In this study, we also found a different distribution pattern of TCR Vβ subfamily T cells, particularly PD‐1+ Vβ subfamily T cells, between M5 and the favorable prognosis subtype M3.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have shown different proliferation patterns of TCR subfamily T cells between different subtypes and different disease statuses in leukemia at the molecular level. 40,41 In this study, we also found a different distribution pattern of TCR V subfamily T cells, particularly PD-1+ V subfamily T cells, between M5 and the favorable prognosis subtype M3. However, there are only 3 cases with M5, so it is hard to perform the statistical analysis; we only observed the trends of alteration of PD-1+ V +T cells in both group, providing preliminary data regarding the association of PD-1+V + CD8+ T cells and the prognosis of AML.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that such T cell immunodeficiencies are characterized by peripheral T cells that are incapable of interacting with blasts, reduced thymic output function, and oligoclonally restricted T cell repertoires, and led to low activation and low antigen responses. Moreover, the immunosuppressive microenvironment, including dysregulation of Th subset cytokines in the bone marrow, where both the innate and adaptive immune responses are profoundly deregulated, sustains and modulates the proliferation, survival, and drug resistance of AML (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The coinhibitory cytotoxic T-lymphocyte associated protein 4 (CTLA-4), which is expressed on activated T cells also binds to CD80 or CD86 and interrupts T cell activation (15,16). After TCR ligation by specific antigens, T cells are stimulated to proliferate and differentiate into the cytotoxic effectors Th1 and Th2 helper cells, regulatory T cells, Th17 cells, or follicular helper T cells, which are influenced by the cytokine milieu and strength and duration of the TCR signal (17,18).…”
Section: Tcr Signaling and Its Regulatory Factorsmentioning
confidence: 99%